The Main Character Development in The King of Staten Island Film - Ramadhan, Aditya Rizky; Zamruddin, Mardliya Pratiwi; Tawakkal, Alamsyah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
The research aimed to analyze the main character development in The King of Staten Island film by using Roberts and Zweig character change theory and Sigmund Freud's structure of personality theory. The researcher used The King of Staten Island film which was released in 2020 by Universal Pictures in association with Perfect World Pictures, and the film script as the source of data. This research used Roberts and Zweig’s character change theory, Sigmund Freud’s structure of personality theories, and Petrie and Boggs film characterization theory to analyze Scott Carlin's character. This research used qualitative method and content analysis approach also Mikos film analysis theory. The researcher confirmed Scott's structure of personality changed before Scott's character developed. Those three elements (id, ego, and superego) supported the character development of Scott Carlin. The result showed the id as the most frequently appeared structure with five data, followed by ego with three data, and lastly followed by superego with three data. It confirmed the id as the part which hinders Scott's development and the ego as the part which influenced Scott's development with the help of certain events in the story as the trigger. The researcher concluded Scott's character development became more courageous, composed, emotionally stable, mature, truthful about his feeling, could heed to other people's advice, control his emotion and anger, overcome his trauma, his hatred towards fireman is gone and admire this profession. On the other hand, the implication was that Scott's relationship with his family was restored, people's view towards Scott changed, and forgiveness of his past mistakes. Key words: Character development, (id, ego, and superego), structure of personality